Interaction of ethylene glycols in aqueous Dimethyl sulfoxide Solutions at different Temperatures (Journal of the College of Basic Education, 2022)
Densities (ρ) and viscosities (η) of ethyleneglycole solutions in the range 0.1 to 0.35 mol dm-3 in 2% and 5% (w/w) Dimethylsulfoxide (DMSO)-water mixtures have been measured at different temperatures (298.15,303.15,308.15 and 313.15 K) .From these experimental data , the apparentmolar volume ϕν,limiting partial molar volume ϕºν, the slop Sν , Jones-Dole A and B-coefficients , Gibbs free energy of activation for viscous flow of solution ∆G*, enthalpy ∆H* and entropy ∆S*were calculated .The results shows a strong ion-solvent interactions and weak ion-ion interactions and also indicate that the ethylene glycole acts as structure breakers.